Communication and location: their interdependencies in contemporary Russian regions - Alexander Pelyasov; Nadezhda Zamyatina (European Regional Science Association (ERSA), 2012)
The main idea of the research is to investigate how the communication processes could result in the location of productive forces in contemporary Russian regions. The results are based on utilizing several traditional and new methods of regional analysis. We have analyzed: 1) Inter-regional skilled migrants flows, including special case of PhD holders (the official statistics of arrivals and departures for all Russian regions for 2008–2010); 2) Internet links between 40 Russian universities' sites (the selected universities are located in 25 Russian cities; the results of more than 1800 retrieval requests were investigated); the number of internet links was compared with the national scientific, educational, and other University ratings; 3) career paths studied on the material of Internet social networks for the case of Tomsk University graduates (more than 1200 students graduated from the University in 2006-2009); 4) location of new biotechnology firms in the cluster of the city of Biysk. We have elaborated several lines of research. 1) Location of the new industries (like biotechnology) and communication pattern between economic actors in this industry. 2) Spatial structure of the Higher Education Institutions in contemporary Russia, their status and mobility patterns of the labor force. 3) Different location behavior among post-graduates of Tomsk University, representing specific assets like specialists in chemistry and physics, and common assets like specialists in arts and applied mathematics. For example the significant portion of specialists in physics born in small towns around Tomsk move to such R&D centers like Snezhinsk and Sarov located more than 1000 km far from Tomsk; the specialists in chemistry born in south cities move to the labor markets of the Russian North; the graduates in arts and applied mathematics tend to stay in Tomsk or to move back to the cities where they were born. 4) Different location behavior among skilled migrants and PhD holders (for example in 2008-2010 PhD holders moved to such peripheral regions as Altai and Kurgan which were losing both the skilled population as a whole and the total population); Regional competitive advantage is closely related with the local communication process. Location or relocation of the most innovative activities depend on the model of local community communication as well as on the scale and substance of its outward communication network.
Keywords: 330